PENGARUH EKSENTRIK EXERCISE UNTUK PENURUNAN NYERI SERTA PENINGKATAN KEKUATAN OTOT PADA KASUS ACHILLES TENDINITIS DI RSUD BAGAS WARAS KLATEN - Ratih Wulandari; Mahendra Wahyu Dewangga; Sri Yunanto (Bajang Institute, 2025)
The gastrocnemius, soleus, and plantaris are the three primary muscles that comprise the Achilles tendon. A common ailment that produces pain at the back of the leg, particularly close to the heel, is Achilles tendinitis. Achilles tendon soreness, edema, and impaired function are common clinical signs that might arise during regular activities as well as during exercise. The researcher employed a case report methodology in this study, involving a patient at the Bagas Waras Klaten Regional Hospital. The patient, who is 65 years old and a carpenter, reported having pain in his left rear leg. Results at T1 = 6 to T4 = 3 showed a reduction in pressure pain following four rounds of therapy. Additionally, there was a reduction in motion pain from T1 = 5 to T4 = 3. Results at T1 = 3 to T4 = 4 show an increase in the strength of the ankle moving muscles during dorsiflexion. Moreover, plantarflexion produced outcomes at T1 = 3 to T4 = 4. According to the findings of the study, patients with Achilles tendinitis benefit from eccentric training in terms of decreased discomfort and increased muscle strength